The Status of Women in Political Participation in Nepal - Pradhan, Prativa (Himalayan Review, 2009)
Nepali women constitute more than half of the country's population. Due to the continuous dominance of the patriarchal value system they remain discriminated and treated as second-class citizens. The current Constitution incorporates specific provisions to provide some political support to women. Despite special measures set by the government for women's political participation, women have not been benefited from such measures. Present paper is an attempt made to analyse status of Nepalese women in various sphere of socio-economic life. Key words: Patriarchal; Constitution; Political participation; Special measures. The Himalayan Review 35-36 (2004-2005) 65-77